Endorsement of Social and Personal Values Predicts the Desirability of Men and Women as Long-Term Partners. (15th November 2017) - Lopes, Guilherme S.; Barbaro, Nicole; Sela, Yael; Jeffery, Austin J.; Pham, Michael N.; Shackelford, Todd K.; Zeigler-Hill, Virgil
A prospective romantic partner's desirability as a long-term partner may be affected by the values that he or she endorses. However, few studies have examined the effects of "values" on a person's desirability as a long-term partner. We hypothesized that individuals who endorse social values (vs. personal values) will be perceived as more desirable long-term partners (Hypothesis 1) and that the endorsement of social values will be especially desirable in a male (vs. female) long-term partner (Hypothesis 2). The current study employed a 2 (sex of prospective partner: male vs. female) × 2 (values of prospective partner: personal vs. social) × 2 (physical attractiveness of prospective partner: unattractive vs. highly attractive) mixed-model design. Participants were 339 undergraduates (174 men, 165 women), with ages varying between 18 and 33 years ( M = 19.9, SD = 3.6), and mostly in a romantic relationship (53.7%). Participants reported interest in a long-term relationship with prospective partners depicted in four scenarios (within subjects), each varying along the dimensions of values (personal vs. social) and physical attractiveness (unattractive vs. highly attractive). Individuals endorsing personal values (vs. social values) and men (vs. women) endorsing personal values were rated as less desirable as long-term partners. The current research adds to the partner preferences literature by demonstrating that an individual's ascribed values influence others' perceptions of desirability as a long-term partner and that these effects are consistently sex differentiated, as predicted by an evolutionary perspective on romantic partner preferences.